Do Freshwater Turtles Use Rainfall to Increase Nest Success? - Geller, Gregory A.; Doody, J. Sean; Clulow, Simon; Duncan, Richard P. (Frontiers in Ecology and Evolution, 2022)
Rainfall following turtle nest construction has long been believed to increase nest survival by its effects on reducing the location cues used by nest predators. However, it is unclear if this is generally the case and if nesting turtles actively use this mechanism to increase their reproductive fitness by deliberately timing nesting to occur before or during rainfall. To address this question, we reviewed studies that examined freshwater turtle nesting behavior and nest predation rates in relation to rainfall. We supplemented our review with data on rainfall and nesting patterns from a 12-year study of two nesting populations of Ouachita Map Turtles (Graptemys ouachitensis). Our review revealed a diversity of responses in rainfall effects on predation and in the propensity for turtles to nest in association with rain. Our mixed findings could reflect a diversity of species- or population-specific responses, local adaptations, species composition of predator community, confounding abiotic factors (e.g., temperature decreases after rainfall) or methodology (e.g., most studies did not quantify rainfall amounts). Our case study on map turtles found very high yearly predation rates (75–100%), precluding our ability to rigorously analyze the association between nest predation and rainfall. However, close examination of the exact timing of both rainfall and predation revealed significantly lower predation rates when rain fell within 24 hrs after nesting, indicating that rainfall during or after nesting may reduce nest predation. Despite this effect, the best fitted model explaining the propensity to nest found that map turtles were more likely to nest after dry days than after days with rainfall, suggesting that rainfall was not a major factor driving turtles to nest in our populations. In both our review and in our map turtle populations there was little evidence that turtles can anticipate rainfall and nest prior to it occurring (e.g., in response to falling barometric pressure).